The Pine Branch, November 1933 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1933)
The Pine Branch. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia. Includes: editorials, photographs, poems, short stories, and other writings.
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education